Leadership in Action In Focus--Retaining and Developing Talent--Generations Talk About Leaders and Leadership Development - D'Amato, Alessia (Center for Creative Leadership, 2009)
A key ingredient in retaining and developing a talented workforce is understanding the expectations of managers.
Title from content provider
Keywords: Leadership